Clinical characteristics and factors associated with mucus plugs under bronchoscopy in children hospitalized for acute asthma attack - Han, Peng; Jiao, Anxia; Yin, Ju; Zou, Huimin; Liu, Yuliang; Li, Zheng; Wang, Quan; Wu, Jie; Shen, Kunling (Frontiers in Pediatrics, 2024)
Objective: To describe clinical characteristics of hospitalized children with acute asthma attacks complicated with mucus plugs and to investigate the factors associated with mucus plugs in asthma children. Methods: This retrospective study analyzed hospitalized children and adolescents with acute asthma attacks from January 2016 to December 2021. The demographic information and characteristics were collected. Subjects were categorized into the mucus plugs group and the control group based on the bronchoalveolar lavage results. The Logistic regression analyses were utilized to assess the relative factors associated with mucus plugs. All data were analyzed using SPSS 22.0. Results: This study included 242 individuals. Out of the 151 subjects who underwent bronchoscopy, 62.9% were classified in the mucus plug group and 37.1% in the control group. The subjects with dyspnea had a higher proportion in the mucus plug group (52.6% vs. 26.8%). The serum total IgE level of the mucus plug group was lower than the control group. The proportion of subjects who were diagnosed with asthma for the first time during hospitalization (87.4% vs. 76.8%) and combined with respiratory infection (91.6% vs. 82.1%) in the mucus plug group might be higher than that in the control group. More subjects in the mucus plug group were administered systemic glucocorticoid, magnesium sulfate, aminophylline, and mucolytic drugs after hospitalization. In multivariable analysis, diagnosed with asthma for the first time during hospitalization (OR=4.404; 1.101-17.614), dyspnea (OR=4.039; 1.306-12.496), and cesarean (OR=0.274; 0.092-0.812) might be associated with mucus plug in children hospitalized for an acute asthma attack. Suggests: While our retrospective study suggest that some clinical features of children hospitalized with asthma who have mucus plugs differ from those without, further studies are required.